LIMBAH KULIT SINGKONG (Manihot utilissima Pohl) SEBAGAI BAHAN ALTERNATIF PASTA BATU BATERAI KERING - Adisti Ratnapuri (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2014)
Utilization and processing of cassava peel waste into a paste of dry batteries associated with the needs of new alternative sources of electrical energy that is being Actively sought and developed along with the development of biotechnology. The purpose of this study was to determine the ability of cassava peel waste to generate electrical energy for use as an alternative material of organic pasta dry batteries. This study used experimental method with two variables: the independent variable ( X ) is the amount of salt usage while the dependent variable ( Y ) is a type of skin cassava Manihot utilissima Pohl with large voltage generated parameters. Data obtained from measurements of a large voltage is processed in the form of a table, and then analyzed by F test using ANOVA (Analysis of Variance). The results showed that the best concentration of salt administration which resulted in average - the highest average by a large voltage is 1.38 volts with a salt concentration of 20 grams of uncooked pasta treatment. ANOVA F test results show that the calculated F is greater than F table 0.05 so that Ho refused and the calculation continued to DMRT (Duncan's Multiple Range Test). These results indicate that there is the effect of salt concentration on the large voltage generated and cassava peel could be used as an alternative to pasta making dry battery.